2020
DOI: 10.1002/eng2.12098
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the type of reinforcement on the physicomechanical behavior of short glass fiber and short carbon fiber‐reinforced polypropylene composites

Abstract: In the present work, short glass fiber (SGF) and short carbon fiber (SCF)‐reinforced polypropylene (PP) composites are fabricated using twin‐screw extrusion and injection molding techniques. The SGF and SCF are reinforced as a single and hybrid reinforcement into the PP matrix with the same weight percentage (wt%) and the obtained composites are characterized for physicomechanical properties. It is observed that the tensile and flexural strength and modulus of elasticity of PP are improved by increasing the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…To achieve the post-treatment of all results, Digital Image Correlation (platform yadics, http://yadics.univ-lille1.fr (19 April 2016)) was used. The compressive modulus was estimated using the measurement of strain fields (Table 4) [24]. The Digital Image Correlation (DIC) method was employed to identify strain/stress localizations [23].…”
Section: Mechanical Testmentioning
confidence: 99%
“…To achieve the post-treatment of all results, Digital Image Correlation (platform yadics, http://yadics.univ-lille1.fr (19 April 2016)) was used. The compressive modulus was estimated using the measurement of strain fields (Table 4) [24]. The Digital Image Correlation (DIC) method was employed to identify strain/stress localizations [23].…”
Section: Mechanical Testmentioning
confidence: 99%
“…The authors concluded that a decrease in strain at break (ductility) is one of the major drawbacks in SCFreinforced thermoplastic composites. In another work 37 on polypropylene composites reinforced with fibers, the authors showed that the incorporation of any content of fiber in polypropylene resulted in a decrease in fracture resistance, causing early failure of the composite. #8.…”
Section: Mechanical Properties Of Pp/pp-g-ma/ Al 2 O 3 /Scf Hybrid Co...mentioning
confidence: 99%
“…The addition to the PP matrix (homopolymer or PP-based copolymers) of reinforcing fibers (e.g., short or long glass fibers, various natural fibers) [ 4 , 11 , 12 , 13 ], nano- and micro-fillers [ 14 ], impact modifiers [ 13 , 15 ], other dispersed phases and special additives, such as flame retardants [ 16 , 17 ], is known as an important route to achieving the enhancement of PP properties required for specific end-use applications, and in some cases, improved processing and cost savings. The mineral-filled (MF) PP compounds can offer enhancements over the unfilled PP, in properties such as stiffness, thermal and dimensional stability, heat deflection at higher temperatures, better processing, and cost-effectiveness [ 18 ].…”
Section: Introductionmentioning
confidence: 99%